Structural properties of hydrogenated amorphous silicon (a-Si:H) thin film grown via radio frequency plasma enhanced chemical vapor deposition (RF PECVD) - 262770 Hasbullah Anthony Hasbi; Zulkafli Othaman, supervisor; Fakulti Sains (2005)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2005